2020
DOI: 10.3390/genes11090960
|View full text |Cite
|
Sign up to set email alerts
|

Immature Immunoglobulin Gene Rearrangements Are Recurrent in B Precursor Adult Acute Lymphoblastic Leukemia Carrying TP53 Molecular Alterations

Abstract: Here, we describe the immunoglobulin and T cell receptor (Ig/TCR) molecular rearrangements identified as a leukemic clone hallmark for minimal residual disease assessment in relation to TP53 mutational status in 171 Ph-negative Acute Lymphoblastic Leukemia (ALL) adult patients at diagnosis. The presence of a TP53 alterations, which represents a marker of poor prognosis, was strictly correlated with an immature DH/JH rearrangement of the immunoglobulin receptor (p < 0.0001). Furthermore, TP53-mutated patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…First, we herein only studied clonal evolution in the IGH locus, but a study on clonal evolution of T-cell receptors might allow deeper insights - particularly as the TRD locus has shown similar recombinase activity as the IGH locus in patients with V H replacement ( 47 ). Second, a recent study has shown that BCP-ALL harboring TP53 alterations are associated with immature DJ H rearrangements ( 48 ). Assuming that TP53 alterations occur already in the pre-leukemic cell compartment, one should study if these cases show clonal evolution rates similar to KMT2A -rearranged cases.…”
Section: Discussionmentioning
confidence: 99%
“…First, we herein only studied clonal evolution in the IGH locus, but a study on clonal evolution of T-cell receptors might allow deeper insights - particularly as the TRD locus has shown similar recombinase activity as the IGH locus in patients with V H replacement ( 47 ). Second, a recent study has shown that BCP-ALL harboring TP53 alterations are associated with immature DJ H rearrangements ( 48 ). Assuming that TP53 alterations occur already in the pre-leukemic cell compartment, one should study if these cases show clonal evolution rates similar to KMT2A -rearranged cases.…”
Section: Discussionmentioning
confidence: 99%